2003
DOI: 10.1103/physrevc.68.054321
|View full text |Cite
|
Sign up to set email alerts
|

C12+C12cluster resonances inet al.

Abstract: The population and decay of excited states in 24 Mg have been investigated using the 12 C͑ 16 O, 12 C 12 C͒␣ reaction at beam energies of 135 and 160 MeV. This measurement permitted the decay spectrum to be measured up to 24 Mg excitation energies of 70 MeV. Resonance structures were observed up to an excitation energy of 49.4 MeV and spin J=18ប. The results are discussed in terms of the termination of a deformed 12 C+ 12 C cluster band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In this respect the alternative reaction 12 C( 16 O, 12 C 12 C)α has been extremely productive. The spectrum in figure 42(a) shows the measurements of the breakup of 24 Mg to two ground state 12 C nuclei at incident 16 O energies of 115 MeV (Freer et al [147]) and 160 MeV [148]. The excitation energy spectrum extends from about 20 MeV up to 55 MeV, and provides evidence for resonant structures persisting to extremely high excitation energies in the 24 Mg system, a remarkable result as complexity might be expected to increase exponentially with excitation energy.…”
Section: Large Di-nuclear Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect the alternative reaction 12 C( 16 O, 12 C 12 C)α has been extremely productive. The spectrum in figure 42(a) shows the measurements of the breakup of 24 Mg to two ground state 12 C nuclei at incident 16 O energies of 115 MeV (Freer et al [147]) and 160 MeV [148]. The excitation energy spectrum extends from about 20 MeV up to 55 MeV, and provides evidence for resonant structures persisting to extremely high excitation energies in the 24 Mg system, a remarkable result as complexity might be expected to increase exponentially with excitation energy.…”
Section: Large Di-nuclear Clustersmentioning
confidence: 99%
“…Figure 42. (a) Resonances observed in the 12 C( 16 O,24 Mg * ) breakup reaction[147,148]. (b) The energy-spin systematics of the breakup resonances, from[148].…”
mentioning
confidence: 99%
“…The most recent study found of the 12 C + 12 C reaction was [21]. We have observed individual levels with neutron energy less than 11 MeV from this reaction at an incident energy of 20 MeV.…”
Section: Symmetric Reactionsmentioning
confidence: 80%
“…As a further near-inverse of radiative capture, break-up reactions are also highly relevant. Breakup of 24 Mg into 12 C-12 C was measured using the 12 C( 16 O, 12 C 12 C)α reaction [39]. Breakup resonances were measured from about 30 to 50 MeV excitation energy in 24 Mg and spin systematics was extracted from the data.…”
Section: How To Advance Experiment?mentioning
confidence: 99%